STAT3, a Key Parameter of Cytokine-Driven Tissue Protection during Sterile Inflammation – the Case of Experimental Acetaminophen (Paracetamol)-Induced Liver Damage - Mühl, Heiko (Frontiers in Immunology, 2016)
Acetaminophen (APAP, N-acetyl-p-aminophenol, or paracetamol) overdosing is a prevalent cause of acute liver injury. While clinical disease is initiated by overt parenchymal hepatocyte necrosis in response to the analgetic, course of intoxication is substantially influenced by associated activation of innate immunity. This process is supposed to be set in motion by release of danger associated molecular patterns (DAMPs) from dying hepatocytes and is accompanied by an inflammatory cytokine response. Murine models of APAP-induced liver injury emphasize the complex role that DAMPs and cytokines play in promoting either hepatic pathogenesis or resolution and recovery from intoxication. Whereas the function of key inflammatory cytokines is controversially discussed, a subclass of specific cytokines capable of efficiently activating the hepatocyte signal transducer and activator of transcription (STAT)-3 pathway stands out as being consistently protective in murine models of APAP intoxication. Those include foremost interleukin (IL)-6, IL-11, IL-13, and IL-22. Above all, activation of STAT3 under the influence of these cytokines has the capability to drive hepatocyte compensatory proliferation, a key principle of the regenerating liver. Herein, the role of these specific cytokines during experimental APAP-induced liver injury is highlighted and discussed in a broader perspective. In hard-to-treat or at-risk patients standard therapy may fail and APAP intoxication can proceed towards a fatal condition. Focused administration of recombinant STAT3-activating cytokines may evolve as novel therapeutic approach under those ill-fated conditions.